Microscopic characterization of some medicinal plants and elemental analysis of Triphala (three fruits) with anticarcinogenic properties - Ghosh, Nabarun; A. Veloz, Mitsy; Sherali, Nelofar; Bandhu Das, Anath; Chatterjee, A.; Bennert, Jeff; Revanna, Chandini (Journal of Medicinal Herbs and Ethnomedicine, 2016)
Medicinal plants are the local heritage and assets to a country that are to be collected, preserved, characterized, scientifically analyzed and utilized in treating particular ailments. Several important medicinal plants from different parts of the world are yet to be indexed, characterized and tested for their medicinal values. Adulteration (mixing cheaper materials with the original herb) is a prime concern in herbal medicine for which proper scientific characterization of specific plant parts of each is essential. In this study characterizationof some medicinally important plant species (Alstonia scholaris,Ephedra sinica,Zingiber officinale,Phyllanthus emblica,Terminalia bellirica, T. chebula) were done. Anatomical studies of transverse sections of the leaves of Adhatoda vasica Nees, stems ofAlstonia scholaris L. R. Br. and Ephedra sinica Stapf.and fine sections of rhizomes from Zingiber officinale Rosc. were carried out.The characteristic presence of typical vascular bundlesfollowing double staining methods and distribution of specific types of tissues helped us to identify and standardize the constant anatomical features. The standardized anatomical features helped us to detect the particular medicinal plants species. A combination of three fruits with medicinal values is called â€˜Triphalaâ€™consisted of â€˜Amlakiâ€™ (Phyllanthus emblica), â€˜Bibhitakiâ€™ (Terminalia bellirica) and â€˜Haritakiâ€™ (Terminalia chebula), used for boosting immunity.Â In the Ayurvedic medicine, Triphala is recommended as an aqueous drink. In this study, microscopic and elemental analyses were attempted for the purpose of identifying morpho-anatomical characteristics of Triphala components, which could serve as markers for the authentication of this herbal product. Thinly cut sections and macerated tissue samples of three fruit samples were mounted in 70% glycerin and observed with a Leica DM-750 microscope equipped with LV-4.4 software. Starch grains, epidermal tissue, and cell wall structures were observed and compared for each species. Brown and yellow storage products, tannin and oil droplets were found in globular cells of T. bellirica and T. chebula. Elemental analysis was carried out using an Elementar CHNS analyzer (vario MICRO cube) to determine total carbon, nitrogen, and sulfur in fruit tissue. The results showed a significant variation in the amounts of carbon between samples.Â